(untitled) (Fiep Bulletin - online, 2014)
The text approaches issues concerning the identification and explanation of terminologies such as profession and professional, looking to clarify points that precede the several divagations on ethics and professional responsibility. However, when dealing with such a theme, it is stressed that in Brazil is dominant the empire of the regulated occupations, created and recognized by Federal Law, which regulates and inspects the operation of the professionals who are registered. Such a procedure is done through the application of Codes of Conduct and Ethics to which every professional, on graduating in her field of knowledge and operating area, is sworn. It is also clear that every intervention by such a professional must follow a sequence of procedures based on scientific and technological knowledge, as well as on her conscience of ethical responsibility. At the final part it is stressed that action, actuation or intervention by any professionals must be based on scientific and technologic knowledge, which will allow to show herself as qualified, competent and able to perform with ethical responsibility the chosen and supporting occupation, thus propitiating cultural transformation - at least within her specialty, the universe of the society involved, becoming then worthy of credit and respect.